Over-Prescription and Overuse of Antimicrobials in the Eastern Mediterranean Region: The Urgent Need for Antimicrobial Stewardship Programs with Access, Watch, and Reserve Adoption - Maha Talaat; Sara Tolba; Enjy Abdou; Mohamed Sarhan; Mohamed Gomaa; Yvan J-F. Hutin (MDPI AG, 2022)
Excessive antimicrobial use contributes to the development of antimicrobial resistance. In the Eastern Mediterranean region (EMR), there is dearth of information on the prevalence of antimicrobial use in patients hospitalized in acute healthcare settings, clinical indications, types of antimicrobials prescribed, and quality indicators for prescriptions. Between September and December 2019, seven countries in the EMR conducted a standardized point prevalence survey. All patients present in the hospital wards at 8 a.m. on the day of the survey constituted the sample population. We collected data, including patient characteristics, antimicrobials received, therapeutic indication according to predefined lists, and markers of prescribing quality. The survey included data from 139 hospitals in seven countries. Among the 19,611 inpatients surveyed, 11,168 patients received at least one antimicrobial {crude prevalence: 56.9% (95%CI: 56.2-57.6%). The top three classes of antimicrobials prescribed were third-generation cephalosporins (26.7%), beta-lactam penicillins (18.1%), and imidazole derivatives (n = 1655, 9.8%). Carbapenems were most frequently prescribed for the treatment of healthcare-associated infections. Compliance with quality indicators of antimicrobial use was limited where treatment guidelines were available for 41% of antimicrobial prescriptions and targeted antimicrobial treatment represented 21% of therapeutic indications. Overall hospital antimicrobial use was high in countries of the EMR, pointing to the need to design and implement context-specific antimicrobial stewardship programs to optimize antimicrobial use and reduce antimicrobial resistance.